Nearly one out of every five adult TB patients suffered from food insecurity in Grawa District, Eastern Ethiopia: a multicenter facility-based cross-sectional study - Abdulla, Jabir H.; Gebremichael, Berhe; Maruta, Melat B.; Yuye, Ibsa; Mohammed, Abdusalam; Debella, Adera; Mussa, Ibsa (Frontiers in Public Health, 2023)
Background: Despite a dramatic decline in tuberculosis mortality over the past ten years, tuberculosis is still the leading cause of death globally. In the last two years, tuberculosis has affected an estimated 10 million individuals, and 1.4 million people have died worldwide. In Ethiopia, the weight of the problem is less known in the study area. As a result, the purpose of this study was to assess food insecurity and associated factors among adult patients with tuberculosis attending public health facilities in Girawa district, Eastern Ethiopia. Methods: A multicenter facility-based cross-sectional study was conducted from March 01 to March 31, 2022, among 488 randomly selected adult tuberculosis patients on treatment follow-up at public health facilities in Girawa district, Eastern Ethiopia. Data were collected using a pre-tested structured questionnaire through a face-to-face interview and document review, entered into Epidata version 3.1, and analyzed using SPSS version 25. The prevalence was reported using a 95% confidence interval (CI) and summary measures. Predictors were assessed using a multivariable logistic regression analysis model and reported using an adjusted odds ratio (AOR) with 95% CI. Statistical significance was declared at a p-value of <0.05. Results: Overall, the prevalence of food insecurity among the study participants was 19.5%, with a 95% CI (15.8%, 23.2%). Factors such as being male [AOR=0.58, 95% CI: (0.34, 0.97)], being married [AOR=2.93, 95% CI: (1.33, 6.47)], being merchant [AOR=0.22, 95% CI: (0.04, 0.67)], having low wealth quintiles [AOR=2.10,95%CI:(1.04-4.23)], receiving anti-TB treatment for two or less months [AOR=0.48, 95% CI: (0.26-0.91)], using Khat [AOR=2.18, 95% CI: (1.29, 3.70)], and Owning livestock (AOR=0.56, 95% CI: 0.29-0.94) were significantly associated with food insecurity. Conclusions: According to this study, nearly one out of every five adults in TB patients is food insecure. Factors such as occupation of the patient, wealth quintiles and using Khat were factors significantly associated with food insecurity. As a result, all stakeholders and concerned entities should prioritize improving the livelihood of TB patients through social security system programs, which are critical to the success of TB control and prevention efforts.